Short-term air pollution exposure decreases lung function: a repeated measures study in healthy adults - Luc Int Panis; Eline B Provost; Bianca Cox; Tijs Louwies; Michelle Laeremans; Arnout Standaert; Evi Dons; Luc Holmstock; Tim Nawrot; Patrick De Boever (BMC, 2017)
Abstract Background Daily changes in ambient concentrations of particulate matter, nitrogen oxides and ozone are associated with increased cardiopulmonary morbidity and mortality, with the lungs and their function being a vulnerable target. Methods To evaluate the association between daily changes in air pollution and lung function in healthy adults we obtained annual lung function measurements from a routine worker health surveillance program not designed for research purposes. Forced Vital Capacity (FVC), Forced Expiratory Volume in the first second (FEV1), FEV1/FVC and Peak Expiratory flow (PEF) from a cohort of 2449 employees were associated with daily measurements of PM10, NO2 and ozone at a nearby monitoring station in the North of Belgium. Repeated measures were available for the period 2011-2015. Results The mean (SD) PM10 concentration on the day of the lung function test was 24.9 (15.5) μg/m3. A 10 μg PM10/m3 increase on the day of the clinical examination was associated with a 18.9 ml lower FVC (95% CI: -27.5 to −10.3, p < 0.0001), 12.8 ml lower FEV1 (−19.1 to −6.5; p < 0.0001), and a 51.4 ml/s lower PEF (−75.0 to −27.0; p < 0.0001). The FEV1/FVC-ratio showed no associations. An increase of 10 μgNO2/m3 was associated with a reduction in PEF (−66.1 ml/s (−106.6 to −25.6; p < 0.001)) on the day of the examination. Conclusions We found negative associations between daily variations in ambient air pollution and FVC, FEV1 and PEF in healthy adults.